PENGARUH DISIPLIN KERJA, KOMPENSASI, DAN BEBAN KERJA TERHADAP KINERJA KARYAWAN - RAHMA HIDAYATI KHAIRI; SYAHRIAN SYAHRIAN (E-Jurnal Manajemen Trisakti School of Management (TSM), 2022)
This study aims to determine the effect of work discipline, compensation, and workload on employee performance. This research was conducted at PT. Bank Rakyat Indonesia Cabang Cikarang, by taking 60 employees as research samples using saturated sampling technique. Collecting data using questionnaires. The data analysis technique used is multiple regression analysis. Based on the study conduct, the results of the analysis showed that work discipline and workload had an effect on employee performance. While compensation has no effect on employee performance